The observation on the level of efficiency on the distribution process of Bantuan Rakyat 1 Malaysia 2.0 (BR1M 2.0) towards the capacity building for Graduates Sarawak (CBG) staffs at Kapit Resident Office / Willie Ak Watson Awan - Watson Awan, Willie (University Technology MARA Sarawak, 2013)
The Resident office of Kapit Division (R7D) was formed on April 2, 1973.The Kapit Division is the seventh of eleven administrative regions in Sarawak and headed by a Resident. The Kapit Division is made up of three districts (Kapit, Song and Belaga) and two sub-districts (Nanga Merit and Sungai Asap). The Resident is responsible for planning, monitoring and supervising the implementation of development programmes in the Division. He is also the head of the Divisional Security Committee. As a chief administrator of the division, he acts as a representative of the State Secretary at the divisional level. Sarawak's system of administrative divisions and districts dates from Rajah Charles Brooke's era. It was he who first divided Sarawak into three divisions on 1 June 1873, both to effectively ensure peace and streamline administration and each had its own Resident in charge. Mainly Englishmen, these Residents were the Rajah's representatives in the area.It were the Resident who had to keep peace among the different warring groups and ensure that Brooke policies were carried out. After the formation of Malaysia on 16 September 1963, the Sarawak State Government assumed administration, retaining the orderly system of divisions. Ten years later, Kapit became a separate division headed by the first Resident, Pancras Eddy Salian.